Mouse-tracking as a tool for investigating strategic behavior in Public Goods Game: an experimental pilot study - Benachour, Asma; Medvedev, Vladimir; Zinchenko, Oksana (Frontiers in Psychology, 2025)
IntroductionRecent research has demonstrated the potential of utilizing mouse-tracking as a viable alternative method for examining attention-related attributes within the context of a multifaceted activity.MethodsIn this study, a mouse-tracking technique was utilized to gather data from individuals who were involved in an online format of the Public Goods Game.ResultsIt was observed that participants exhibited distinct approaches to acquiring information while formulating decisions to propose high, moderate, or low offers. The mouse-tracking algorithm effectively distinguished between various types of offers made toward group funding, as evidenced by the measured distance of the cursor.DiscussionThese findings suggest that mouse-tracking is a valuable tool for capturing decision-making processes and differentiating behavioral patterns in economic game contexts, offering insights into attention and choice mechanisms.